The macrocyclic lactone oxacyclododecindione reduces fibrosis progression - Saurin, Sabrina; Meineck, Myriam; Rohr, Markus; Roth, Wilfried; Opatz, Till; Erkel, Gerhard; Pautz, Andrea; Weinmann-Menke, Julia (Frontiers in Pharmacology, 2023)
Background: Renal fibrosis is one of the most important triggers of chronic kidney disease and only a very limited number of therapeutic options are available to stop fibrosis progression. As fibrosis is characterized by inflammation, myofibroblast activation and extracellular matrix deposition, a drug that is able to address all these processes might be an interesting therapeutic option. Methods: We tested in kidney tubular epithelial cells (HK2 cell line and primary cells) and in vivo in an ischemia reperfusion (I /R) model in C57BL/6 mice, whether the natural product oxacyclododecindione (Oxa) reduces fibrosis progression in kidney disease. This was evaluated by western blot, mRNA expression, and mass spectrometry secretome analyses as well as by immunohistochemistry. Results: Indeed, Oxa blocked expression of epithelial-mesenchymal transition marker proteins, reduced renal damage, immune cell infiltration and collagen expression and deposition, both in vitro and in vivo. Remarkably, the beneficial effects of Oxa were detected also when the natural product was administered at a time point of established fibrotic changes, a situation that is close to the clinical situation. Initial in vitro experiments demonstrated, that a synthetic Oxa derivative possess similar features. Conclusion: Although open questions such as possible side effects need to be investigated, we believe that the combination of anti-inflammatory and anti-fibrotic effects of Oxa make the substance a promising candidate for a new therapeutic approach in fibrosis treatment and therefore the prevention of progression of kidney disease.